2012
DOI: 10.1053/j.gastro.2012.05.046
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Therapy Does Not Reduce Pain in Patients With Chronic Pancreatitis: The ANTICIPATE Study

Abstract: Publisher's copyright statement: NOTICE: this is the author's version of a work that was accepted for publication in Gastroenterology. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reected in this document. Changes may have been made to this work since it was submitted for publication. A denitive version was subsequently published in Gastroenterology, 143/3, 2012Gastroenterology, 143/3, , 10.105… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
89
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(91 citation statements)
references
References 19 publications
0
89
0
2
Order By: Relevance
“…72 However, the recent completion of the ANTI-Oxidant therapy for painful Chronic Pancreatitis Therapy Evaluation (ANTICIPATE) study concluded that patients with painful chronic pancreatitis of alcoholic origin did not experience a reduction in pain or improvement in quality of life with combined antioxidant therapy, despite a sustained increase in blood levels of the antioxidants. 73 The authors mentioned that their cohort consisted of older patients (median 50 years versus 30 years in the study by Bhardwaj et al) who likely had irreversible pancreatic damage that could not be modified by antioxidant supplementation. 72 These findings are similar to the results obtained by Burton et al who found that administration of antioxidants was more effective in younger patients and those with a pancreatitis etiology secondary to idiopathic and obstructive versus alcoholic pancreatitis.…”
Section: Antioxidants and Herbal Supplementsmentioning
confidence: 99%
“…72 However, the recent completion of the ANTI-Oxidant therapy for painful Chronic Pancreatitis Therapy Evaluation (ANTICIPATE) study concluded that patients with painful chronic pancreatitis of alcoholic origin did not experience a reduction in pain or improvement in quality of life with combined antioxidant therapy, despite a sustained increase in blood levels of the antioxidants. 73 The authors mentioned that their cohort consisted of older patients (median 50 years versus 30 years in the study by Bhardwaj et al) who likely had irreversible pancreatic damage that could not be modified by antioxidant supplementation. 72 These findings are similar to the results obtained by Burton et al who found that administration of antioxidants was more effective in younger patients and those with a pancreatitis etiology secondary to idiopathic and obstructive versus alcoholic pancreatitis.…”
Section: Antioxidants and Herbal Supplementsmentioning
confidence: 99%
“…Antioxidant treatment is a strategy to treat pain in chronic pancreatitis. There are conflicting data, however, whether a 5-component antioxidant cocktail (containing selenium, beta-carotene, vitamin C, vitamin E, and methionine) reduces pain in chronic pancreatitis (37)(38)(39)) but there appears to be a modest reduction in the frequency of pain in patients with deficiencies of antioxidants and/ or antioxidant-scavenging enzymes and increased markers of oxidative stress (37). Targeting PPAR gamma signaling could potentially simultaneously treat multiple pancreatic (and perhaps extra-pancreatic) derangements, in part due to interactions between the endocrine and exocrine pancreas; in a nonobese model of insulin resistance, PPAR-gamma treatment abolished impairments of both pancreatic endocrine function (insulin resistance) and pancreatic exocrine function in mice (40).…”
Section: S41 Role Of Cftr In Normal Exocrine Pancreatic Functionmentioning
confidence: 99%
“…Although there are international and national guidelines for the management of chronic pancreatitis, the evidence for selection of suitable treatment modalities is less clear [1]. In terms of baseline treatments, there is a series of relatively small randomised trials evaluating treatments such as the role of alcohol avoidance counselling in preventing re-admission in the early stages of the disease, gabapentin for symptom control and micronutrient antioxidant therapy [2-4]. In terms of further treatment, there are small randomised trials comparing endoscopic treatment to surgical intervention, but a large part of the body of evidence on either endoscopic or surgical treatment derives from case series reporting outcome [5-6].…”
Section: Introductionmentioning
confidence: 99%